Conformação da questão social que alicerça o trabalho doméstico sobre a força de trabalho das mulheres negras em Sergipe - Ramos, Mayara Augusta Monteiro (2022)
Within the Marxist perspective, it is not possible to understand the social question without considering the exploitation of labor by capital. However, the social question as a result of the extraction of added value is concretely presented through its various expressions. Expressions that can only be understood in the mediation with work, from which the racism present in social relationships can be apprehended, whether through unemployment, informality and/or the precariousness of work relationships. In this perspective, the present study aims to analyze the conformation of the social issue that underpins domestic work in Sergipe on the black women's workforce. It is about discussing some of the traits assumed by the social issue in Sergipe, from which it is possible to understand the bases that structure domestic work and its foundation on the female and black workforce. The research started from the registration forms of the workers inserted in the Casa da Doméstica Dom José Vicente Távora, between the years 2018 and 2020. It is an exploratory research, with a qualitative approach and that refers to the historical-dialectical materialism. For a better understanding of the proposed objectives, documental and bibliographic research were used. The results of the investigation showed that the conservative character of the transition from slave to free labor in Sergipe, in its contemporary developments, gives continuity to the place of black women in the productive structure of class society; regional inequality, which is an integral part of the causal complex that structures unemployment in the State, reinforces domestic work as the alternative found for racially discriminated women who migrate to urban centers; and the concentration of land that is the basis of unemployment, poverty and rural-city migration are historical-structural determinants of the social issue in Sergipe that build the foundations of domestic work in the State. By analyzing these historical-structural determinants, in their articulations, it can be said that they form the most structuring traits of the social issue in Sergipe and, in this sense, constitute the foundations of domestic work. Foundations built on the black women's workforce.